Retrospective cohort study of all deaths among infants born between 22 and 27 completed weeks of gestation in Switzerland over a 3-year period. Issue 6 (15th June 2017) - Berger, T M; Steurer, M A; Bucher, H U; Fauchère, J C; Adams, M; Pfister, R E; Baumann-Hölzle, R; Bassler, D
Abstract : Objectives: The aim of this research is to assess causes and circumstances of deaths in extremely low gestational age neonates (ELGANs) born in Switzerland over a 3-year period. Design: Population-based, retrospective cohort study. Setting: All nine level III perinatal centres (neonatal intensive care units (NICUs) and affiliated obstetrical services) in Switzerland. Patients: ELGANs with a gestational age (GA) <28 weeks who died between 1 July 2012 and 30 June 2015. Results: A total of 594 deaths were recorded with 280 (47%) stillbirths and 314 (53%) deaths after live birth. Of the latter, 185 (59%) occurred in the delivery room and 129 (41%) following admission to an NICU. Most liveborn infants dying in the delivery room had a GA ≤24 weeks and died following primary non-intervention. In contrast, NICU deaths occurred following unrestricted life support regardless of GA. End-of-life decision-making and redirection of care were based on medical futility and anticipated poor quality of life in 69% and 28% of patients, respectively. Most infants were extubated before death (87%). Conclusions: In Switzerland, most deaths among infants born at less than 24 weeks of gestation occurred in the delivery room. In contrast, most deaths of ELGANs with a GA ≥24 weeks were observed following unrestricted provisional intensive care, end-of-life decision-making and redirection of care in the NICU regardless of the degree of immaturity.